2007
DOI: 10.1063/1.2430487
|View full text |Cite
|
Sign up to set email alerts
|

In Ga N ∕ Ga N nanostripe grown on pattern sapphire by metal organic chemical vapor deposition

Abstract: The authors have used metal organic chemical vapor deposition to grow InGaN∕GaN multiple quantum well (MQW) nanostripes on trapezoidally patterned c-plane sapphire substrates. Transmission electron microscopy (TEM) images clearly revealed that the MQWs grew not only on the top faces of the trapezoids but also on both lateral side facets along the [0001] direction defined by the selected area electron diffraction pattern. Meanwhile, dislocations that stretched from the interfaces between the GaN and the substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…However, the multiple-step regrowth process is too complicated and time consuming. In addition to ELOG and PE, several groups have proposed that direct lateral epitaxial growth on patterned sapphire substrates (PSSs) can simplify the growth process and enhance device performance and efficiency [8][9][10][11]. In our previous work [11], we have demonstrated that GaN grown on patterned r-plane sapphire substrates with asymmetrically inclined facets can have a very low-defect density (10 7 cm À2 ) in GaN epilayers without regrowth process.…”
Section: Introductionmentioning
confidence: 96%
“…However, the multiple-step regrowth process is too complicated and time consuming. In addition to ELOG and PE, several groups have proposed that direct lateral epitaxial growth on patterned sapphire substrates (PSSs) can simplify the growth process and enhance device performance and efficiency [8][9][10][11]. In our previous work [11], we have demonstrated that GaN grown on patterned r-plane sapphire substrates with asymmetrically inclined facets can have a very low-defect density (10 7 cm À2 ) in GaN epilayers without regrowth process.…”
Section: Introductionmentioning
confidence: 96%
“…Commonly, metal silicide contacts, especially NiSi, have been used to reduce the resistance for bulk and SOI FET. However, the lateral diffusion of Ni to form NiSi in SiNW is still unknown (1)(2)(3)(4). In this paper, evaluation of lateral Ni diffusion into SiNW has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental studies indicate that a further reduction in the defect density is possible if the lateral overgrowth approach is reduced to nano-scale [12,13]. Nanostructure devices may also play an important role in overcoming the existing dislocations and difficulties encountered in light extraction [14]. In this study, we describe the fabrication and characteristics of GaNbased LEDs on nano-patterned sapphire substrates (NPSSs) and demonstrate the enhancement of the light output power of LEDs on NPSSs over conventional LEDs on the planar sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%